Teachers' motivational perceptions and students' academic achievement at Oman public schools - Al-Rawahi, Talal Salim Sangoor; Che Hassan, Norlizah; Ismail, Asmah (Human Resource Management Academic Research Society, 2018)
Motivation is an essential factor which affects students’ participation and engagement in their classwork and academic achievement and grades. The main purpose of this research is to identify the level of teacher motivational perception and investigated the differences of motivational perception based on genders, grade level teach and teaching experiences. This study is a correlational survey design consisting questionnaires by Hardre’ (2008), Teacher Motivational Perception (TMP) to obtain data from the respondents. A pilot study have been conducted on 30 teachers which indicates the scores of Cronbach's Alpha for TMP (?=.74). The study sample comprised of 135 Welayate Sumail, Al Dakhelia Governorate teachers, who taught grade 11th and 12th.. Overall, there were 64 male and 71 female teachers who taught core subjects with five years of minimum teaching experience. Results showed that there was a moderate teachers’ motivational perception (M=3.29, SD=.327 and moderate level of students’ academic achievements (M=66.29, SD=7.11. There are significant differences in teacher motivational perception based on gender (t=1.137, p=.032) and class levels (F=3.928, p=.019) but no significant difference (x^2=2.008, p>0.05) in teaching experiences. The findings of this study may serve as a platform for school authorities, administrators and policymakers to develop students’ motivation and motivational strategies that can be practised in Oman public schools.